Hubungan Terpaan Media SosialInstagram @exploreBali Dengan Niat Berwisata Followers @exploreBali ke Bali - Christy, Bella; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT In this era of increasingly sophisticated technology, humans no longer spread information only through printed media. But also through the internet media. One of them is social media like @exploreBali, an Instagram account that inform Bali’s tourist destinations. The purpose of this study was to determine the correlation between exposure of @exploreBali social media Instagram with the intention of @exploreBali’s Instagram followers to visit Bali. This research uses quantitative method. Sampling technique used in this research is non-probability sampling and the method is purposive samplng. Data were obtained by distributing questionnaires. The results showed that there is a correlation between exposure of @exploreBali social media Instagram with the intention of @explorebali followers to visit Bali. The direction of correlation between the variables of @exploreBali Social Media Instagram with @exploreBali followers intention to travel to Bali is known to be positive and unidirectional. Which means the more frequent @exploreBali’s followers is exposed to @exploreBali social media Instagramthen the intention of @exploreBali’s followers to travel to Bali will be higher. On the other hand, this research shows only the conviction indicator is high, while the purchase indicator is relatively low. Keywords: Social Media Exposure, Instagram, @exploreBali, Travel Intentions. Correlations